Kompetensi Pedagogik Guru Bahasa Arab Madrasah Aliyah Se Kota Samarinda - Mustamin Fattah (FENOMENA, 2013)
This is a field research which aimed at describing the level of pedagogic competency of Arabic teachers at Madrasah Aliyah in Samarinda. The sample of this research are 8 Arabic teachers from 5 madrasah both state and private madrasah. The data collection techniques used observation, interview, and questionnaires. The data were analyzed using Miles and Hubberman. The findings of study show there are three indicators to measure the level of pedagogic competency; self perception, vice headmaster of curriculum’s perception, and students’ perception. In the level of self perception, it was found that the teachers’ pedagogic competency is 3.8; it indicated the category ”Good”. In the level of vice headmaster of curriculum’s perception, it was found that the teachers’ pedagogic competency is 3.9; it indicated the category ”Good”. In the level of the students’ perception, it was found that the teachers’ pedagogic competency is 4.1; it indicated the category ”Good”.